Primary production assessment on eco-engineering infrastructures: English Channel case study. Issue 1 (1st July 2022) - Claquin, P; Vivier, B; Navon, M; Rusig, A M; Mussio, I; Chasselin, L; Deloor, M; Dauvin, J C; Boutouil, M; Orvain, F
Abstract: In the Marineff project, experimental eco-engineering dyke modules were immersed in 2020 in the Bay of Cherbourg (English Channel). Eco-engineering and classic dyke modules were compared regarding biodiversity and productivity. This paper presents the monitoring strategy of primary production assessment applied. Primary production assessment was performed by coupling various technics in order to consider all the compartments of primary producers present on the dykes and in the associated surrounding water mass. Seaweeds, microphytobenthos and phytoplankton were studied. Benthic chambers measuring oxygen and pCO2 under controlled light, and technics based on variable fluorescence were applied on eco-engineering and classic dyke modules. Preliminary results are presented in order to illustrate the expected indicator and methodology improvement and limits were discussed. The whole data set will allow us to explore the relationship between productivity and biodiversity as a function of the sites and of the nature of the infrastructure, eco-engineering or not. At this stage of our study we pointed out that the macroalgae were 7.9 times more productive than biofilm per surface on eco-engineering module whilst only 1.5 times on classic module. Smooth surface appeared to favour biofilm productivity at this stage of colonisation while rough surface drove more quickly the system to a production dominated by macroalgae.